USING SMALL GROUP DISCUSSION AS LEARNING INTERACTIONS TO IMPROVE THE STUDENTS’ SPEAKING ABILITY AT THIRD SEMESTER IN ENGLISH DEPARTEMENT OF UNIVERSITAS MUHAMMADIYAH MAKASSAR - Andi Asri Jumiaty; Dzur Ri’fah (Elite : English and Literature Journal, 2017)
This research aims to find out the improvement the students’ ability in speaking. The speaking skills are complex and sometimes difficult to teach, the problem of the students have a lot of ideas in their minds but they worry to start and even they don't know how to develop ideas in teaching techniques can improvestudents’ ability in speaking English. To solve this problem, the English teacher should have to be more creative in choosing the material and techniques which can make the speaking class more interesting, exciting and enjoyable.            This research focuses using small group discussion because it is very important to achieve speaking skill. For this reason, the researcher tries to see the students’ participation and improve their speaking skills through small group discussion. The researchers assume that small group discussion will be interesting because the students will be more active and this assumption is however still in question, whether or not, the students of English department Muhammadiyah University of Makassar can take part and improve their speaking skills through small group discussion.  ABSTRAK            Penelitian ini bertujuan untuk mengetahui peningkatan kemampuan berbicara mahasiswa. Keterampilan berbicara sangat kompleks dan terkadang sulit untuk diajarkan, masalah para mahasiswa memiliki banyak ide dalam pikiran mereka tetapi mereka khawatir untuk memulai dan bahkan mereka tidak tahu bagaimana mengembangkan ide dalam teknik mengajar dapat meningkatkan kemampuan mahasiswa dalam berbahasa Inggris. Untuk mengatasi masalah ini, dosen bahasa Inggris harus lebih kreatif dalam memilih materi dan teknik yang dapat membuat kelas berbicara lebih menarik dan menyenangkan; tujuan dari penelitian adalah bagaimana siswa meningkatkan kemampuan berbicara mereka.            Penelitian ini berfokus pada penggunakan diskusi kelompok kecil karena sangat penting untuk mencapai keterampilan berbicara. Untuk alasan ini, peneliti mencoba untuk melihat partisipasi mahasiswa dan meningkatkan keterampilan berbicara mereka melalui diskusi kelompok kecil. Peneliti beranggapan bahwa diskusi kelompok kecil akan membuat mahasiswa tertarik karena mahasiswa akan lebih aktif dan  mahasiswa jurusan bahasa Inggris Universitas Muhammadiyah Makassar dapat mengambil bagian dan meningkatkan kemampuan berbicara mereka melalui kelompok diskuai kecil. Kata kunci: diskusi kelompok kecil, keterampilan berbicara.